Getting the most out of college - Bennett, Margaret E. (New York : McGraw Hill Education, 1957)
Awareness of the urgent need for enlightened and responsible citizenship in our democracy has led to strong emphasis upon the discovery and fostering of talent. College students are a potential source of trained and responsible leadership for all the various aspects of living.
Chapter 1. Getting acquainted -- Chapter 2. What are you looking for? -- Chapter 3. Learning to learn -- Chapter 4. Learning self-direction -- Chapter 5. Learning about yourself -- Chapter 6. Charting a life plan -- Chapter 7. Developing a life philosophy.
Includes bibliographical references and index.
Keywords: COLLEGE STUDENT